Transmigration and urban social work: towards a research agenda. Issue 1 (2nd January 2016) - Schrooten, Mieke; Geldof, Dirk; Withaeckx, Sophie
Abstract : Many Western European countries, and especially the larger cities within these countries, are making a transition towards super-diversity. This shift towards super-diversity is also characterised by a growth of the phenomenon of transmigration, whereby people frequently move back and forth across borders. The social life of transmigrants is not only oriented towards their country of residence, but also consists of complex networks beyond boundaries. Transmigrants constantly shift between different modus operandi and between different visible and invisible, local and global networks. Many transmigrants face a high risk of social vulnerability and are overrepresented in the client population of urban social services. Although much research has been done on transmigration on the one hand, and on international social work on the other hand, the effect of transmigration on social workers and on social work practice is still under-investigated. Based on social work research in Brussels and Antwerp, the authors research the challenges transmigration poses to social work. They demonstrate that there is a difference in perspective between the translocal and transnational lives of transmigrants on the one hand versus the locally rooted practices of social workers on the other hand. Using this analysis as a springboard, they identify a number of avenues for additional inquiry in this field.